The Ability of the Brain Grows Throughout Life? - Tamonaga, Masanori (Nihon Rōnen Igakkai zasshi, 1986)
The human species had acquired the relatively longest lifespan among the animals by developing their intelligence. There are various data which indicate that the cerebral cortical function does not decline with age, e. g. in the healthy persons the glucose utilization is well preserved in the cortex by PET study, and dendritic arborization of the hippocampus is also well developed in the aged, especially in the persons with good intelligence. The capacity to develop the nerve process could be observed also in vitro study by culture of aged nerve cells. On the other hand, in order to prevent a decline of intelligence, several risk factors for brain aging should be controlled: cerebrovascular disease, senile dementia, disorder of sensory organs, e.g. vision and hearing, somatic and sociopsychological changes, and nutritional unbalance.